2015
DOI: 10.1259/dmfr.20140365
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between DICOM-calibrated and uncalibrated consumer grade and 6-MP displays under different lighting conditions in panoramic radiography

Abstract: DICOM calibration may improve observer performance in panoramic radiography in different lighting conditions. Therefore, a DICOM-calibrated consumer grade display can be used instead of a medical display in dental practice without compromising the diagnostic quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
2
1
Order By: Relevance
“…The interval window length is longer than the more commonly reported two weeks, however it is approximately half that of some other studies which reviewed images after at least six months. 2,17,18 In two studies by Hellén-Halme et al 19,20 they reported intraobserver agreement ranging from fair to moderate, which was similar to our restored molar agreement. 19,20 However our intraobserver agreement was significantly higher than Hellén-Halme et al 19,20 for the primary caries detection on the premolar, which was observed to be from moderate to almost perfect.…”
Section: Chapter 3 Resultssupporting
confidence: 89%
“…The interval window length is longer than the more commonly reported two weeks, however it is approximately half that of some other studies which reviewed images after at least six months. 2,17,18 In two studies by Hellén-Halme et al 19,20 they reported intraobserver agreement ranging from fair to moderate, which was similar to our restored molar agreement. 19,20 However our intraobserver agreement was significantly higher than Hellén-Halme et al 19,20 for the primary caries detection on the premolar, which was observed to be from moderate to almost perfect.…”
Section: Chapter 3 Resultssupporting
confidence: 89%
“…These findings were inconsistent with other studies that found significantly higher preference for MD in identifying some anatomic structures and diseases. 13,14 Furthermore, the detection of specific abnormalities based on different imaging modalities showed no significant differences between the screens in the present study. On the other hand, Kallio-Pulkkinen et al 13 showed a significantly higher preference in favor of MD for the detection of pathologic lesions.…”
Section: Discussioncontrasting
confidence: 46%
“…preference. 14,15 Most of the aforementioned studies have limited clinical value because they failed to provide the impact on observer preference in relation to multiple dental abnormalities. They were focused instead on single dental anomalies acquired with only one type of imaging modality.…”
Section: Statement Of Clinical Relevancementioning
confidence: 99%
“…32 In these studies, 31,32 the ambient light level was set between 25 and 40 lx. Recently, Kallio-Pulkkinen et al 33 concluded that the DICOM-calibrated consumer grade display is adequate for the detection of anatomical structures and pathology in panoramic radiographs also in bright (510 lx) ambient light. 33 In the present study, the DICOM-calibrated consumer grade display was significantly better for the interpretation of enamel caries in lower and upper molars and dentinal caries in lower molars in bright lighting and in dentinal caries in lower molars in both lighting conditions.…”
Section: Discussionmentioning
confidence: 99%